The ‘Practical Approach to Lung Health’ in sub-Saharan Africa: a systematic review - Banda, H. (Int J Tuberc Lung Dis, 2016)
SETTING: There is a high burden of respiratory disease in sub-Saharan Africa. To address this problem, the World Health Organization launched the ‘Practical approach to Lung Health’ (PAL), i.e., locally applicable integrated syndromic algorithms, to improve primary care management of these diseases. OBJECTIVE: To examine the evidence for the impact of PAL on the diagnosis and management of tuberculosis (TB) and other common respiratory problems in sub-Saharan Africa. DESIGN: A systematic review of MEDLINE (1998–2015), EMBASE (1998–2015) and CINAHL (1998–2015) was conducted to find trials evaluating PAL implementation in sub-Saharan Africa. RESULTS: Five studies were found, evaluating three PAL variations: PAL in South Africa (PALSA), PALSA with integrated human immunodeficiency virus treatment (PALSA PLUS) and PAL in Malawi using lay health workers (PALM/LHW). PALSA increased TB diagnosis (OR 1.72, 95%CI 1.04–2.85), as did PALSA PLUS (OR 1.25, 95%CI 1.01–1.55). Cure or completion rates in retreatment cases in PALSA and PALSA PLUS were significantly improved (OR 1.78, 95%CI 1.13–2.76). PALM/LHW, which examined TB treatment success, found no significant improvement (P = 0.578). CONCLUSION: The limited research performed shows that PAL can be effective in TB diagnosis and partial treatment success; however, more evidence is needed to assess its effects on other respiratory diseases, especially in wider sub-Saharan Africa.